Multi-Objective Process Optimization for Overpressure Reflow Soldering in Electronics Production - Esfandyari, Alireza (FAU University Press, 2025)
Surface Mount Technology (SMT) is the primary method of permanently mounting electronic components on a substrate. A decisive improvement in the quality of the connection technologies is achieved by increasing the reliability of the solder joints and reducing heat dissipation. The soldering oven technology in combination with an overpressure module enables void-free solder joints. However, the configuration of the process-related mechanism has not yet been fully investigated. In addition, the method offered in the market is energy-intensive, and a deep understanding of the resource flow into the process is mandatory if minimization of consumption is to be achieved. This study deals with a multi-criteria/overall optimization solution based on a trade-off model for quality, energy, cost and time criteria. The approach to find the optimal solution for each criterion is possible. However, a holistically optimized multi-criteria solution is not possible. Using significance analysis a criteria approach for the overpressure soldering process is defined to maximize or minimize each goal/criterion using Artificial Neural Network (ANN) modeling approach. A compromise model has been developed, which enables the decision maker to achieve the setup goal while considering the conflicting requirements in the best possible approach.